2015
DOI: 10.1111/opo.12206
|View full text |Cite
|
Sign up to set email alerts
|

Healing indicators after pterygium excision by optical coherence tomography

Abstract: Results: Eleven eyes displayed lesion recurrence (R group) and 62 eyes showed no recurrence (NR group). Normal anatomical structures, corneal and conjunctival epithelium and limbal demarcation area, were identified by OCT images in a higher percentage of NR cases over time, compared to the R group where most of the cases held without these markers of tissue recovery. In contrast, the variable graft thickening, which analyzed a pathological event, revealed similar results in both groups (p>0.05; Fisher's exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…OCT images 6 months postoperatively showed well defined limbal demarcation zone in Rgroup as compared to NRgroup. Therefore, spectral domain OCT well established the 6 sequential changes in % progressive tissue recovery after pterygium excision, not only it identified earliest changes related to complete healing of corneal, conjunctival epithelium & limbal demarcation zone but also earliest changes, which were leading to pterygium recurrence (18). In our study mitomycin-C was not used, operative AS-thickness found recurrence pterygium and ultraviolet radiation: a positive correlation.…”
Section: Resultssupporting
confidence: 54%
“…OCT images 6 months postoperatively showed well defined limbal demarcation zone in Rgroup as compared to NRgroup. Therefore, spectral domain OCT well established the 6 sequential changes in % progressive tissue recovery after pterygium excision, not only it identified earliest changes related to complete healing of corneal, conjunctival epithelium & limbal demarcation zone but also earliest changes, which were leading to pterygium recurrence (18). In our study mitomycin-C was not used, operative AS-thickness found recurrence pterygium and ultraviolet radiation: a positive correlation.…”
Section: Resultssupporting
confidence: 54%
“…Even though sensitivity is decreased in pterygium-affected corneas [15,16], no previous investigations have studied how corneal sensitivity is related to lesions in the corneal nerve fibers in patients with pterygium. Moreover, several studies have reported that corneal sensitivity recovers before reinnervation after corneal surgery [26,27]. erefore, in the present study, we investigated both the corneal subbasal nerve plexus and corneal sensitivity to determine whether functional changes are related to any anatomical modification.…”
Section: Introductionmentioning
confidence: 93%
“…Richdale et al 13 provide strong evidence supporting the use of OCT to measure lens thickness in vivo, providing a foundation for the potential clinical use of OCT for this purpose. In addition, Pujol et al 14 suggest that OCT imaging of the corneal epithelium and limbus can predict healing success in patients following pterygium excision.…”
mentioning
confidence: 99%